System verification : proving the design solution satisfies the requirements - Grady, Jeffrey O. (Academic, 2007)
Systems Engineering--an interdisciplinary, multi-stage-driven approach to the design and implementation of any large-scale or complex engineered product or service--has found its way from aerospace into general manufacturing as well as the services industry. It has been found to be particularly useful in such applications as software engineering, the bio- and medical industries, and large, multi-component projects like those found in energy-generation. Following on the authors previous book System Requirements Analysis, this new book will lay out the steps and procedures needed to implement a quality check of the system being proposed or designedthe Verification stage of a full systems engineering program. Systems engineering usually begins with defining a product that will satisfy a customer need and then rationally building a set of required components, personnel, and financial resources. The testing and evaluating of a proposed design solution is known as Verification, and this will guide the systems engineer and his engineering and management team in setting up the detailed protocols for a step-by-step quality control check of each stage of a proposed system design. Complete overview of the basic principles involved in setting up a System Verification program Follows a proven pattern of "Define the problem, "Solve the Problem," and "Prove it" Covers a variety of approaches to Qualification Verification, System Test and Evaluation, and Acceptance Verification, as well as Process Verification